A Facile Method for Selection of Solvents for Fabrication of Polypropylene Membranes by Thermally Induced Phase Separation. Issue 2 (1st February 2022) - Pochivalov, Konstantin V.; Basko, Andrey V.; Lebedeva, Tatyana N.; Yurov, Mikhail Yu.; Yushkin, Alexey A.; Volkov, Alexey V.
Abstract: This article presents a rapid method for selecting solvents suitable for polymer membrane formation by thermally induced phase separation. The method, based on optical microscopy, makes it possible to determine temperatures of liquid-liquid phase separation and polymer crystallization in the blends and to monitor structural changes in the blends during cooling. The proposed method was applied to find out whether a series of disubstituted esters of dicarboxylic acids and their binary mixtures could be used to form polypropylene membranes. The obtained polymer crystallization temperatures and liquid–liquid phase separation temperatures in the different mixtures were used to compare the thermodynamic affinity of the chosen solvents for polypropylene. The results were compared to the data on Hildebrand solubility parameters. It is shown that the thermodynamic affinity of dialkyl phthalate for polypropylene increases as the alkyl-substituent becomes longer, while the comparison of the Hildebrand solubility parameters gives quite unambigiuous results depending on the value chosen for the polymer.